Efeito do método pilates versus exercícios físicos supervisionados em indivíduos com síndrome pós-COVID-19 - Jorge, Matheus Santos Gomes (2023)
Post-COVID-19 syndrome, also known as long COVID, is described as a chronic condition, whose symptoms related to SARS-CoV-2 infection persist, or manifest, for a period equal to or greater than twelve weeks. Fatigue, physical deconditioning, chronic pain, muscle weakness and lung changes are some of the most reported symptoms and significantly impact the functional capacity, quality of sleep and quality of life of these individuals. The literature is consistent about the role of physiotherapy in the recovery of individuals with post-COVID-19 syndrome, especially through supervised physical exercise. However, few studies have explored the potential of the Pilates Method in the rehabilitation of this population. In this context, the objective of this thesis was to verify the effects of the Pilates Method versus supervised physical exercises in individuals with post-COVID-19 syndrome. The first two scientific productions presented are randomized clinical trials with a blind evaluator and came from a single project called "Physiotherapy intervention in individuals with post-COVID-19 syndrome", approved by the Research Ethics Committee of the University of Passo Fundo (number 5,320 .280). Fifty-nine individuals with post-COVID-19 syndrome were randomly assigned to three groups: Pilates group (GP; n=20), whose participants performed exercises specific to the method in solo mode and with specific equipment; supervised physical exercise group (GEF; n=20), whose participants performed a combined exercise protocol (resistance, aerobic, balance, proprioception and flexibility) in a gym; and control group (CG; n=19), whose participants received unsupervised home guidance. GP and GEF interventions took place individually, twice a week, for eight weeks, totaling 16 sessions. The main outcomes analyzed in the first production were physical fitness (six-minute walk test), post-exercise fatigue (modified Borg scale) and sleep quality (Pittsburgh Sleep Quality Index), while the main outcomes analyzed in The second output was pain (visual analogue scale) and muscle strength of the lower and upper limbs (30-second sit-to-stand test and manual dynamometry, respectively). Statistical analysis was conducted through "intention to treat" using paired samples t-test and one-way analysis of variance (ANOVA) with Tukey post-hoc. The significance level adopted was 5%. The third scientific production presented was a systematic review with meta-analysis on the effects of the Pilates Method on individuals with post-COVID-19 syndrome. The search was carried out in the databases PubMed/MEDLINE, PEDro, SciELO, LILACS, Scopus, Web of Science, ScienceDirect and Cochrane Library, in addition to Google Academic and the CAPES repository, for studies published until September 2023. The review was paired and the risk of bias and methodological quality were assessed using the Cochrane Risk of Bias 2.0 tool and the PEDro scale, respectively. The meta-analysis was carried out using the Review software Manager version 5.4 (Cochrane Collaboration), using the random effects model. As a result, this thesis generated three scientific productions that were prepared in accordance with the guidelines of international journals to which they were sent. In summary, both the Pilates Method and supervised physical exercises improved physical health parameters, with the Pilates Method improving sleep quality in individuals with post-COVID-19 syndrome. Furthermore, the Pilates Method was superior to supervised physical exercises in terms of physical conditioning and home-based guidance in terms of post-exercise fatigue. These findings suggest that the Pilates Method may be a strategy to be considered in the treatment of individuals with post-COVID-19 syndrome.